A Survey On The Implementation Of Fine Motoric Portfolio Assessment Of Children Aged 4-6 Years By Kindergarten Teachers In Pare Sub-District - Yudha, Rivo Panji; Ayuni, Fatkhul Jannah Putri (Universitas Muhammadiyah Ponorogo, 2024)
This research aimed to describe the implementation of fine motor portfolio assessments for children aged 4-6 years by kindergarten teachers in Pare Sub-district, Kediri Regency, East Java. This research used quantitative methods, where researchers took a cross-sectional type survey. This type refers to research that can be carried out by collecting data only once. The population in this study were kindergarten teachers in Pare Sub-district, totalling 45 schools. The research results showed that 18 kindergarten teachers in Pare District carried out the fine motor portfolio assessment of children aged 4-6 years very well, 23 teachers carried out the fine motor portfolio assessment of children aged 4-6 years well, while 5 teachers assessed the fine motor portfolio of children aged 4-6 years quite well. The average (mean) score of respondents from the research results on the implementation of children's fine motor portfolio assessments by kindergarten teachers in Pare District, Kediri Regency, East Java, was 77.02. The teacher's portfolio assessment has followed the portfolio assessment stages. The stages for assessing portfolios of kindergarten teachers in Pare Sub-district are determining (1) the objectives of the portfolio, (2) the contents of the portfolio, and (3) the criteria and format for the assessment. The teachers did not involve children or parents in assessing the fine motor portfolio of children aged 4-6 years.